Effect of rose water on structural, optical and electrical properties of composites of reduced graphene oxide–poly (vinyl alcohol) (PVA) grafted with silver nanoparticles. (13th February 2017) - Kumar, Devender; Wadhwa, Heena; Mahendia, Suman; Chand, Fakir; Kumar, Shyam
Abstract: In this work, nanocomposites of reduced graphene oxide–poly (vinyl alcohol) (PVA) grafted with silver nanoparticles (rGO-PVA-Ag) were prepared in the absence and presence of rose water. The optical characterizations of prepared nanocomposites were done through UV–visible spectroscopy and Transmission Electron Microscopy (TEM) and Raman spectroscopy was employed for the surface characterization. The grafted silver (Ag) nanoparticles are found to be almost spherical in shape with reduction in their mean diameter from 47 nm to 26 nm after addition of rose water. The UV–visible absorption spectra of as-prepared rGO-PVA-Ag nanocomposites without and with rose water depicted surface plasmon resonance (SPR) peak at around 448 nm which coincides with the predicted spectra from simulation based on the Mie Theory. The electrical dc conductivity measurements as the function of temperature from room temperature to 55 °C were investigated. It has been found that use of rose water in synthesis process increases the electrical conductivity of the rGO-PVA-Ag. The mode of the electrical conduction in the composites can be explained using Efros–Shklovskii Variable Range Hopping mechanism (ES VRH).